Penghitungan Tebal Setara Metode Boussinesq-Exel dan FWD-ELMOD pada Perkerasan Lentur - Hardwiyono, Sentot (Semesta Teknika, 2012)
Calculating the Flexible Pavement System (FPS) response has initiated by Boussinesq, Burmister, Huang and more scientists around the world. Determining modulus elasticity each stratum FPS very important to note to designing the Flexible Pavement. The purpose of this study is to determine the elastic modulus of each layer in the profile Flexible Pavement Systems (FPS) with a thickness equivalent method Boussinesq-Exel and FWD-ELMOD. Tests were run on the Soekarno-Hatta Cikampek-Purwakarta-Bandung and West Java highways, Indonesia. The test results showed a good correlation between the modulus of each layer in the FWD testing with those of Boussinesq-Exel test.